2016
DOI: 10.1097/md.0000000000005729
|View full text |Cite|
|
Sign up to set email alerts
|

Stereotactic radiotherapy in neovascular age-related macular degeneration

Abstract: Stereotactic radiotherapy (SRT) is a new approach to treat neovascular age-related macular degeneration (nAMD). The INTREPID trial suggested that SRT could reduce the frequency of regular intravitreal injections (IVIs) with antivascular endothelial growth factor drugs, which are necessary to control disease activity. However, the efficacy of SRT in nAMD and resulting morphological changes have not been validated under real-life circumstances, an issue, which we would like to address in this retrospective analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…For the current case, we report the extension of anti-VEGF treatment intervals during the first 2 years following adjunct SRT with stable VA. This corresponds to the findings of the INTREPID trial as well as a few real-life analyses [ 5 , 6 , 10 , 11 , 12 ]. However, like several patients in a real-life case series [ 8 ], our patient experienced the necessity of shortening of anti-VEGF treatment intervals in the third year after SRT.…”
Section: Discussionsupporting
confidence: 84%
“…For the current case, we report the extension of anti-VEGF treatment intervals during the first 2 years following adjunct SRT with stable VA. This corresponds to the findings of the INTREPID trial as well as a few real-life analyses [ 5 , 6 , 10 , 11 , 12 ]. However, like several patients in a real-life case series [ 8 ], our patient experienced the necessity of shortening of anti-VEGF treatment intervals in the third year after SRT.…”
Section: Discussionsupporting
confidence: 84%
“…3 shows that the number of subjects in the IRay group that didn’t require further injections following the loading phase was nearly double that of the control group (45.5 vs. 24.0%, P = 0.005). While the IRay group likely contained responders to anti-VEGF therapy, the additional 21.5% of patients requiring no further injection is similar to the 33% of patients in the best-responding subgroup of INTREPID and the 25% of patients in a real life study of patient’s pre-verses post-IRay therapy [8, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Other treatment modalities under investigation include the role of adjunctive treatments alongside anti-VEGF by stereotactic radiotherapy (ie, use of a low-voltage external beam) to reduce the frequency of intravitreal injections needed while maintaining VA. 175 , 176 Ranjbar et al 177 demonstrated that the mean number of intravitreal injections was reduced by almost 50% during the 12 months after stereotactic radiotherapy compared to the number required the year before and that VA increased by one line (logMAR). Other promising therapeutic approaches are modulators of angiogenesis.…”
Section: Treatment Of Wet Amdmentioning
confidence: 99%